2018
DOI: 10.1093/ibd/izx113
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Endoscopic Resections of Large Laterally Spreading Colorectal Lesions in Inflammatory Bowel Disease: a Single United Kingdom Center Experience

Abstract: This cohort series demonstrates that endoscopic resection of large non-polypoid lesions associated with colitis is feasible and safe using an array of resection methods supporting the role of advanced endoscopic therapeutics for the management of colitis associated dysplasia in a western tertiary endoscopic center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…The strength of this systematic review of videoendoscopic era studies is that it has attempted to clarify the risk of dysplasia progression to advanced neoplasia and specifically the risk of metachronous advanced neoplasia after endoscopic resection of colitis‐associated dysplasia in the videoendoscopic era. In addition, this review has identified a further 20 studies not included in Fumery et al's meta‐analysis 31,33‐38,40‐46,51‐54,56,57 . The wide variation in outcomes demonstrated by our systematic review may be explained by a number of factors.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The strength of this systematic review of videoendoscopic era studies is that it has attempted to clarify the risk of dysplasia progression to advanced neoplasia and specifically the risk of metachronous advanced neoplasia after endoscopic resection of colitis‐associated dysplasia in the videoendoscopic era. In addition, this review has identified a further 20 studies not included in Fumery et al's meta‐analysis 31,33‐38,40‐46,51‐54,56,57 . The wide variation in outcomes demonstrated by our systematic review may be explained by a number of factors.…”
Section: Discussionmentioning
confidence: 85%
“…These are technically difficult procedures performed by a small number of specialist endoscopists for high‐risk lesions. Description of histological R0 resection success and intensive post‐polypectomy surveillance intervals are strictly adhered to in these more recent studies, which have demonstrated that achieving R0 resection and adhering to close follow‐up by expert endoscopists are associated with a lower risk of metachronous advanced neoplasia than previously thought 41‐46,54 . Therefore, although of low quality, the evidence supports the practice of continued close surveillance of patients following successful R0 resection of dysplastic lesions.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations